1995
DOI: 10.1016/0014-5793(95)00190-k
|View full text |Cite
|
Sign up to set email alerts
|

Diaminoalkanes with an odd number of carbon atoms induce compaction of a single double‐stranded DNA chain

Abstract: ~bstract We have performed direct observations on the conformational change of a single double-stranded T4 DNA molecule induced by diaminoalkanes, NH~(CH2).NH~ (n = 1 -6), by use of fluorescence microscopy. It was found that diamines with three and five methylene groups show a significant effect on the compaction of individual single DNA molecules. On the other hand, diamines with two, four and six methylene groups are not effective in the compaction of DNA. Such a drastic difference in the action of diamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…We have experimentally confirmed that the fluorescence dye, Gelgreen, at the adapted concentration exhibits negligible effect on the conformation of DNA molecules, referring to the past studies on the higher-order structure of DNA. [25][26][27][28][29][30][31] All observations were carried out at room temperature (24 • C).…”
Section: B Dna Conformation In Solution As Observed By Fluorescence mentioning
confidence: 99%
See 1 more Smart Citation
“…We have experimentally confirmed that the fluorescence dye, Gelgreen, at the adapted concentration exhibits negligible effect on the conformation of DNA molecules, referring to the past studies on the higher-order structure of DNA. [25][26][27][28][29][30][31] All observations were carried out at room temperature (24 • C).…”
Section: B Dna Conformation In Solution As Observed By Fluorescence mentioning
confidence: 99%
“…Nevertheless, divalent cations also cause shrinkage of the DNA chain at relatively high concentrations of several to several tens of mM. 27 In usual biological systems, polyamines with 3 or 4 positive charges and divalent metal cation, such as Mg(2+) or Ca(2+), are typical poly-cationic species. Thus, it may be of interest to clarify the effect of the coexistence of multivalent polyamines and divalent metal cations on the higher-order structure of a giant DNA molecule.…”
Section: Introductionmentioning
confidence: 99%
“…48 We found that giant DNA molecules undergo an on/off transition from an expanded coil state to a compact state accompanied by a difference in density on the order of 10 4 -10 5 upon the addition of various condensing agents including polyamines, 40,41 basic proteins, 49 and neutral polymers, 50 while short DNA fragments behave like rigid rods and cannot undergo such a folding transition. 4,38,51 Here, we extended our investigation to a megabase-size genomic DNA (S120-1 DNA) that was successfully extracted from Rhodoligotrophos appendicifer (strain 120-1 T = JCM 16873 T = ATCC BAA 2115 T ).…”
Section: Introductionmentioning
confidence: 97%
“…38 Over the past decade, we have investigated the changes in the higher-order structure of a large DNA molecule through a single-molecule observation using FM. [39][40][41][42][43][44][45][46][47] To visualize individual DNA molecules, we used T4 phage DNA (166 kbp) as a model large DNA, and its size is on the order a) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 99%
“…Diaminoalkanes with three and five methylene groups have been reported to be more effective than diamines with two, four, and six methylene groups [80].…”
Section: Formulation Parametersmentioning
confidence: 99%